ANALISIS TINGKAT DAN FAKTOR PENYEBAB DEPRESI SE ASIA TENGGARA - Hervina Nathasya; Putri Nuraini; Siti Zahara At Thohiroh; Tiara Salma; Fadhlina Rozzaqyah (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Depression is a serious global health problem, ranking as the 4th most common illness in the world. The high prevalence of depression in the world and Southeast Asia makes it urgent to conduct research related to depression rates and contributing factors in the region. This study used the Systematic Literature Review (SLR) method to analyze various national and international articles. The results of the analysis show that the highest rate of depression in Southeast Asia occurs in the adolescent group. This can be attributed to adolescence being a transition period from childhood to adulthood, where individuals experience various physical, emotional, and social changes.